The Last Word - H.C. Marais (Communicare)
WHAT should the role of communications be in a situation like the one experienced In South Africa? The recent research on Inter- group relations concluded that tension would probably always be endemic in a deeply divided society. Reform should be priority number one, but in order to be "suc- cessful" It should be the outcome of par- ticipation and joint decision making